Hanan Catering's Instagram promotions, pricing, and menu variety influence consumer purchasing decisions in Bandung - I Nyoman Tri Sutaguna; Chevy Herli Sumerli A; Geofakta Razali; Muhammad Yusuf (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the effect of promotions on Instagram, prices and menu variety on purchasing decisions for Hanan Catering in Bandung City. This research approach uses the approachscientificto test the justification of the proposed hypothesis. The population in this study were all consumers of homemade birthday cakes in Bandung. The sampling technique for determining the sample to be used in this study uses the techniquenon probability sampling, that ispurposive sampling. Then the total sample in this study was 91 respondents. The results of the study found that promotions on Instagram, prices and menu variety both simultaneously and partially have a positive and significant effect on purchasing decisions.